PENGARUH TRANSFER PRICING, PROFITABILITAS, KEPEMILIKAN INSTITUSIONAL DAN FINANCIAL DISTRESS TERHADAP PENGHINDARAN PAJAK - Muhammad Aldy Saputra; Hasnawati Hasnawati (Jurnal Ekonomi dan Bisnis, 2023)
Taxes are the biggest source of income in Indonesia. Indirect tax contributions will be received back benefits for the development of a country through government spending and development of the country's infrastructure. In the implementation of tax revenues, in practice it turns out that there are companies that take tax avoidance measures to minimize corporate tax payments. Tax avoidance can have an impact on decreasing state revenues which in turn can have an impact on the planning and implementation of the state budget. Given the important role of tax revenue, it is necessary to test and analyze the factors that can influence tax avoidance. The purpose of this research is to analyze the effect of transfer pricing, profitability, institutional ownership and financial distress on tax avoidance. This study uses purposive sampling method as a research method and uses multiple regression analysis models. The results of the research show that transfer pricing, profitability and institutional ownership have an influence on tax avoidance. Meanwhile, financial distress has no effect on tax avoidance